About the publication of "the Russian-Lithuanian calendar" for 1873-1876 - Vytautas Merkys (Knygotyra)
Until now, it was incorrectly stated that the Calendar was published periodically for 1873-1876 (compiled by I. Kretchinskij). As far as we know, not a single copy of this Calendar has been preserved (a slight mention in a Milovidov booklet from 1908 remains the basis of this article).